The Role of Culture in the Development of Society and the Opportunities to Finance It in Russia - Lazareva, Galina Ivanovna; Efremova, Lyudmila Anatolyevna; Rusetskaya, Elvira Antsasovna; Ulibina, Lubov Konstantinovna; Okorokova, Olga Alekseevna (Journal of History Culture and Art Research, 2018)
In a civilised society a point of view on acknowledging culture as one of the most significant resources of socio-economic development was formed. The development of culture in Russian society faces multiple problems. In "The Fundamentals of the Legislation of the Russian Federation on Culture" the duties and responsibilities of state administration bodies for the effective development of this sphere and financial support of cultural activity are proclaimed. Defining the boundaries of state regulation of financial relations in culture and leisure sphere is mainly dependant on the type of social and budgetary policy of the state that influence directly the degree of implementing the declared priorities and on the guarantees to the population of a country in the field of culture. These problems constitute the subject matter of the given research. The condition of the objects of culture and the list of tasks that are solved with its assistance prove the necessity to specify the methodological principles of implementing the state policy in the sphere of culture. The elements of scientific novelty consist in justifying the necessity to develop a complex of measures of improving forms and methods of financial support of culture with the use of the elements of functionally oriented financing of industry expenses.